Preventive Effect of Nutrition Support on Peroneal Neuropathy in Cancer Patients - Fukuda, Hiroyuki; Yamashita, Aiko; Imai, Toru; Tsumaki, Hiromi; Nagata, Namiko; Ishikawa, Hiroshi; Niihara, Masahiro; Tsubosa, Yasuhiro; Onozawa, Yusuke (Frontiers in Nutrition, 2019)
Background: The occurrence of peroneal neuropathy was reported to be higher in cancer patients than in non-cancer patients. Cancer patients should have their nutritional intake carefully managed in order to minimize weight loss and avoid the occurrence of peroneal neuropathy. However, the effect of nutrition support on the prevention of peroneal neuropathy is not understood. Aims: The present study aimed to assess epidemiologically the effect of nutrition support on the occurrence of peroneal neuropathy in cancer patients. Methods: We performed a retrospective case-control study in 178,597 cancer patients admitted to Shizuoka Cancer Center Hospital from 2002 to 2017. The rates of peroneal neuropathy were assessed between the eight-year period before nutrition support started and the seven-year period during which nutrition support performed. Results: Twenty-nine and 14 cases of peroneal neuropathy occurred in the periods without and with nutrition support, respectively. Compared with the period without nutrition support, the risk of peroneal neuropathy decreased by 62% during the period with nutrition support (odds ratio, 0.38; 95% confidence interval, 0.18 -0.74; P<0.05). Conclusion: Our study suggests the preventive effects of nutrition support on peroneal neuropathy in cancer patients.